Juvenile wood in Populus deltoides `Stoneville 67´: analysis of density variation in the stem. - Cobas, A. C. (Universidad Nacional del Litoral, 2022)
The objective of the present work was to determine the age of transition from juvenile to mature wood from the study of the axial and radial variation of density and to carry out descriptive models of distribution of juvenile and mature wood in the stem of Populus deltoides, clone `Stoneville 67´ of 20 years of age. The density presented an increase in its values from the medulla to the cortex and from the base to the apex. The transition age was determined between 10-12 years of age, the volume of juvenile and mature wood was 40% and 60%, respectively. The distribution of juvenile wood coincided with the central cylinder model.